Safety and efficacy of a feed additive consisting of Allura Red AC for small non‐food‐producing mammals and ornamental birds (Versele‐Laga). (17th December 2021) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Allura Red AC for small non‐food‐producing mammals and ornamental birds when used as an additive that add or restore colour in feedingstuffs. The use of Allura Red AC up to the proposed conditions of use of 500 mg/kg complete feed is considered safe for guinea pig, chinchilla, degu, hamster, gerbil and chipmunk. The following maximum safe levels (mg/kg complete feed) apply to the following species: ferrets 99, rabbits 123, canaries, budgerigars, mynah and toucans 45, lovebirds 51, cockatiels 79, cockatoos 115, amazons 145, parrots 147, yellow breast macaw 150, blue‐throated macaw 173 and hyacinth macaw 214. The maximum safe level of Allura Red AC for other small non‐food‐producing mammal is 99 mg/kg feed and for other ornamental birds is 45 mg/kg feed. Inhalation exposure of Allura Red is regarded as hazardous. In the absence of data, the Panel cannot conclude on the potential of Allura Red to be a skin/eye irritant or a skin sensitiser. The FEEDAP Panel cannot conclude on the efficacy of the additive.